Annexin A1 (ANXA1): a systematic review of its role in inflammation - Sanggavi Nadarajan,; Norazrina Azmi,; Malina Jasamai,; Endang Kumolosasi, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Inflammation is a body response towards any injury or tissue damage. It involves the accumulation of neutrophils and release of inflammatory mediators. ANXA1, a 37 kDa glucocorticoid inducible protein plays an important role in resolving inflammation. The unique N-terminal and its mimetic peptide exert strong anti-inflammatory actions. This study was conducted to review the roles of ANXA1 in inflammation and identify any other reported roles. Electronic search was done whereby a total of 3797 articles were located from three databases, namely Ovid MEDLINE, Science Direct, and PubMed. Articles on ANXA1 and inflammation were selected based on inclusive criteria and review papers were excluded. Bias analysis was performed based on bias risk tool and 27 articles were included in the study. It was found that ANXA1 was able to resolve inflammation in many inflammatory diseases. Upon treatment with glucocorticoid, ANXA1 is induced and its significant expressions in tissues are important in resolving inflammation. However, this effect can be reversed by administering an anti-annexin antibody. This protein also acts on members of all formyl peptide receptors (FPR) and activates them to initiate reaction. It acts mainly by causing the death of neutrophils through apoptosis. In addition, ANXA1 is identified as a marker in cancer cells which determines the survival rates. In conclusion, ANXA1 is a key modulator in resolving inflammation in many diseases and is actively being induced upon glucocorticoid treatment.